Robust control of adaptive power quality compensator in Multi-Microgrids for power quality enhancement using puzzle optimization algorithm - Sindi, Hatem F.; Alghamdi, Sultan; Rawa, Muhyaddin; Omar, Ahmed I.; Hussain Elmetwaly, Ahmed (Ain Shams Engineering Journal, 2023)
The primary purpose of this paper is to design a novel multi-microgrid connection that uses power compensation methods to improve voltage profiles and reduce harmonic distortions using specific compensation devices in low inertia systems. The utilized compensation device is an adaptive power quality compensator (APQC) which includes series and shunt compensators. Thyristor controlled series capacitor (TCSC) is used as a series compensator to alleviate the dynamic voltage profile as well as diminish transient voltage. A shunt active power filter (SAPF) is utilized as a shunt compensator to improve the power factor and lessen voltage and current harmonics. The TCSC has a power level of error of the PID controller, while the SAPF has a dynamic multi-level of errors of the PID controller. Further, the recent swarm intelligence-based puzzle optimization algorithm is employed to get the best self-tuning of the PID controller gains to reveal the act of the APQC typology. The efficacy of the presented APQC with the multi-level mechanism approach, assessed using Matlab/Simulink time-domain simulations, has been compared with the recently reported literature. Two operation modes are addressed, one for the island mode and the other for the grid-connected mode with significant renewable generation penetration and nonlinear loads. APQC successfully enhances the power quality of multi-microgrids (MMGs), according to theoretical research and simulation statistics. Finally, three comparative study assessments of numerous optimization approaches, with a unified power flow conditioner (UPFC), and with other series-shunt compensators like distributed power condition controller (DPCC) are proposed to attain efficacy and strength of the compensator.